ChemInform Abstract: Hydrothermal—Thermal Conversion Synthesis of Hierarchical Porous MgO Microrods as Efficient Adsorbents for Lead(II) and Chromium(VI) Removal. Issue 50 (16th December 2014) - Zhang, Linlin; Zhu, Wancheng; Zhang, Heng; Bi, Siwei; Zhang, Qiang
Abstract MgO microrods with hierarchical porous structure (ranging from micropores to meso‐ and macropores) and well‐defined rod‐like morphology are prepared via a flux (NaCl) and surfactant (nonylphenol polyoxyethylene ether, NP‐9) directed thermal decomposition (porcelain boat, 650, 2 h) of hydrothermally grown MgC2O4·2H2O microrods (autoclave, 180 °C, 3 h).